Silver nanoparticles and cellulose microfiber micro-composite from banana (Musa acuminata) waste: green synthesis, antioxidant property and antimicrobial capacity - Alvarado-Aguilar, Chanena (2023)
The green chemistry promotes the synthesis of nanomaterials from plant extracts as a new climate intelligent alternative to the use of conventional protocols based on costly and toxic chemicals. Therefore, this research was undertaken to analyses the efficiency of banana (peels and rachis) waste extracts in the production of a micro-composite composed by silver nanoparticles (AgNPs) and cellulose microfibers (CMF) respectively. Results showed the synthesis of 24 nm diameter spherical particles AgNPs, with a peak of absorbance at 410 nm, in (v/v) water:ethanol extracts of banana peels at a final dilution of 3.10-2. Concomitantly, 50-350 µm in length and 5-10 µm of diameter CMF were obtained via the oxalic acid hydrolysis of the oven-dried banana rachis. The micro-composite (AgNPs-CMF) and AgNPs displayed an active reducing capacity over 60% determined by the DPPH test, and active bacterial activity against E. Coli and S. aureus in Petri dishes. Overall results support the use of banana waste for the synthesis of AgNPs and CMF for industrial purposes.